Firearm-Related Homicide in Sweden: A Latent Class Analysis of Suspected Offenders - Khoshnood, Ardavan (Crime & delinquency, 2023)
Sweden has witnessed a significant increase in the rate of firearm-related homicide. We therefore aimed to study the characteristics of individuals suspected of homicide, attempted homicide, preparation to commit homicide as well as conspiracy to commit homicide with a firearm in Sweden. By using information from different registers, suspected individuals between 2000 and 2017 and aged 15 to 60 were included in the study. A total of 889 individuals were evaluated. A notable part were females (5.1%). Latent Class Analysis identified three classes, where two classes were high-offending-classes, and one class was a low-offending-class. The identification of these classes may be used for more effective preventive measures.